7 - De la présence féminine dans la rue : Stratégies d’accession à l’espace public dans un quartier spontané, Ras El Ain – Oran (Algérie) - Mehdi Souiah, (African Sociological Review, 2019)
Ras El Ain, a spontaneous neighborhood part of the poor periphery of the city of Oran (Algeria), is here apprehended as a cultural area (as would say the researchers of the School of Chicago). An area that sort its occupants, and thereby «imposes» a sum of practices and confers «roles». Both men and women are social roles that take place and are cultivated on a daily basis. This text aims to shed light on the balance of power (domination) that is exercised between the sexes within a social group (inhabitants of the neighborhood), and this through an analysis of the daily life of women (professionally inactive, mainly). In this neighborhood where the weight of tradition remains relatively heavy, women use strategies that allow them to access the outdoor space, ie how do these women negotiate their exit? What are the trade-offs (with society and its traditions) that they use to reach the public space and practice it?